2016
DOI: 10.1002/14651858.cd006937.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Speech therapy for children with dysarthria acquired before three years of age

Abstract: This review found no evidence from randomised trials of the effectiveness of speech and language therapy interventions to improve the speech of children with early acquired dysarthria. Rigorous, fully powered randomised controlled trials are needed to investigate if the positive changes in children's speech observed in phase I and phase II studies are generalisable to the population of children with early acquired dysarthria served by speech and language therapy services. Research should examine change in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 66 publications
(4 reference statements)
1
12
0
2
Order By: Relevance
“…Treatment should involve learning or skill acquisition (e.g., as evidenced by improved intelligibility), mode of delivery should be intensive and should include significant repetitions and opportunities for practice, and task complexity should increase over time. Traditional CP treatments that do not implement these key elements have been ineffective in treating children with CP and dysarthria [Pennington et al, ]. Our results strengthen the evidence for neuroplasticity following LSVT LOUD [Liotti et al, ; Narayana et al, ].…”
Section: Resultssupporting
confidence: 81%
“…Treatment should involve learning or skill acquisition (e.g., as evidenced by improved intelligibility), mode of delivery should be intensive and should include significant repetitions and opportunities for practice, and task complexity should increase over time. Traditional CP treatments that do not implement these key elements have been ineffective in treating children with CP and dysarthria [Pennington et al, ]. Our results strengthen the evidence for neuroplasticity following LSVT LOUD [Liotti et al, ; Narayana et al, ].…”
Section: Resultssupporting
confidence: 81%
“…[1][2][3] Rapid advances in discovery are anticipated over the coming decade, unraveling the complex genetic, environmental, and neural origins. [23][24][25][26][27][28][29] What is the clinical course?…”
Section: Sources and Selection Criteriamentioning
confidence: 99%
“…Recruitment may not be representative of Trusts in other parts of the UK. However, to our knowledge no research is being conducted on children’s speech elsewhere in the UK and there is sparse research internationally 20. Families participating in this study used their own laptops/tablets for the remote therapy and may represent a ‘tech-savvy’ group.…”
Section: Discussionmentioning
confidence: 99%
“…Small-scale studies of therapy to control respiratory effort for speech and coordinating exhalation with phonation to generate a clearer speech signal and a steady speech rate have shown increases in intelligibility, utterance duration and communicative participation 16–19. However, as yet no randomised controlled trials (RCT) of this type of intervention for children with cerebral palsy have been reported 20…”
Section: Introductionmentioning
confidence: 99%